Silybins are stereospecific regulators of the 20S proteasome. (15th July 2022) - Persico, Marco; García-Viñuales, Sara; Santoro, Anna Maria; Lanza, Valeria; Tundo, Grazia Raffaella; Sbardella, Diego; Coletta, Massimiliano; Romanucci, Valeria; Zarrelli, Armando; Di Fabio, Giovanni; Fattorusso, Caterina; Milardi, Danilo
Graphical abstract: Abstract: A reduced proteasome activity tiles excessive amyloid growth during the progress of protein conformational diseases (PCDs). Hence, the development of safe and effective proteasome enhancers represents an attractive target for the therapeutic treatment of these chronic disorders. Here we analyze two natural diastereoisomers belonging to the family of flavonolignans, Sil A and Sil B, by evaluating their capacity to increase proteasome activity. Enzyme assays carried out on yeast 20S (y20S) proteasome and in parallel on a permanently "open gate" mutant (α3ΔN) evidenced that Sil B is a more efficient 20S activator than Sil A. Conversely, in the case of human 20S proteasome (h20S) a higher affinity and more efficient activation is observed for Sil A. Driven by experimental data, computational studies further demonstrated that the taxifolin group of both diastereoisomers plays a crucial role in their anchoring to the α5/α6 groove of the outer α-ring. However, due to the different stereochemistry at C-7" and C-8" of ring D, only Sil A was able to reproduce the interactions responsible for h20S proteasome activation induced by their cognate regulatory particles. The provided silybins/h20S interaction models allowed us to rationalize their different ability to activate the peptidase activities of h20S and y20S. Our results provide structural details concerning the important role played by stereospecific interactions in driving Sil A and Sil B binding to the 20S proteasome and may support future rational design of proteasome enhancers.